Hubungan Pengetahuan Dan Sikap Ibu Terhadap Kemampuan Toilet Training Pada Anak Usia Toddler Di Kelurahan Bungus Timur - Eliwarti (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2024)
There are still many mothers who have not taught toilet training in toddler age children due to the knowledge of the mother is still low and the lack of information obtained from health personnel. . In order for toilet training skills to run well, there needs to be a real understanding and attitude about toilet training from parents especially mothers, because the mother is the closest to the child. The purpose of this study is to determine the relationship of knowledge and attitude of mother to the ability of toilet training at toddler age children in Sub East Bungus Year 2017. The type of this research is analytic descriptive with cross sectional study design. This research was conducted in 3 Posyandu of Sub East Bungus in October 2016-June 2017. The population was 136 people and the sample was 76 respondents with total sampling technique. The result showed that the ability of toilet training was less good in low maternal knowledge (76.7%), and negative mother’s attitude (75.0%). There is a significant correlation between knowledge (p= 0,002) and mother attitude (p= 0,005) to toilet training capability in toddler age child. Keywords : Knowledge; Attitude; and Toilet training